1987
DOI: 10.1080/03014468700006892
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of Punjabi children aged 6–12 years

Abstract: The study aims at evaluating the growth performance of primary school children of Patiala (Punjab, India) belonging to lower and lower middle socio-economic groups, with special emphasis on the effects of social class and urbanization. Cross-sectional data on 1380 children (656 boys and 724 girls) ranging in age from 6 to 12 years were collected during 1974. Dimensions measured were height, weight, circumferences of chest and upper arm, triceps, subscapular and suprailiac skinfolds. Standard techniques (Weiner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Availability of nutrients and medical health care in India, at present, is JOURNAL Scatter plot of adjusted target height (aTH) z-score against child's height z-score in the lower socioeconomic class. As a result, people from villages are migrating to cities where per capita income and standard of living is higher 6 In our study, as in other studies, parents and children in the LSC were significantly shorter than their USC counterparts, and the USC children were also significantly taller, heavier and had a higher BMI 14 . 11,2005 Brought to you by | University of California -San Francisco Authenticated Download Date | 2/20/15 9:18 AM best in the urban USC, followed by the urban LSC, and is least in the villages 13 .…”
Section: Discussionsupporting
confidence: 78%
“…Availability of nutrients and medical health care in India, at present, is JOURNAL Scatter plot of adjusted target height (aTH) z-score against child's height z-score in the lower socioeconomic class. As a result, people from villages are migrating to cities where per capita income and standard of living is higher 6 In our study, as in other studies, parents and children in the LSC were significantly shorter than their USC counterparts, and the USC children were also significantly taller, heavier and had a higher BMI 14 . 11,2005 Brought to you by | University of California -San Francisco Authenticated Download Date | 2/20/15 9:18 AM best in the urban USC, followed by the urban LSC, and is least in the villages 13 .…”
Section: Discussionsupporting
confidence: 78%
“…After adjusting for age and sex, anthropometric data from all but three centres (A, B and D) were comparable, with mean(SD) values ~0 (1), suggesting that the socio-demographics of most subjects included in this study were representative of well-nourished South-Asian children throughout India and the UK. As previously reported from a study of Punjabi children[ 36 ], South-Asian children from Northern India (Centre B) were taller and heavier than those from other centres. Whereas both anthropometry and lung function were lower in children from semi-urban/rural areas when compared with their urban counterparts in centre A, height and weight z-scores remained significantly lower in subjects from Centre D (Hyderabad) despite excluding all data from subjects from middle/low SEC, potential reasons for which could not be ascertained retrospectively.…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, they are also smaller than the differences in growth status that have been found between the highest and lowest social strata in Venezuela (Lopez Contreras de Blanco et al, 1985;Lopez Blanco et al, 1987;Mendez Castellano, 1985;Landaeta-Jimenez et al, 1991). Martorell and Habicht (1985) and Singh et al (1987) reported the same observation, suggesting similarity in the socioeconomic structure of urban and rural samples as an explanation. In fact, 97% of the Venezuelan rural sample and 79% of the urban sample belong to the two lowest strata (Strata IV and V).…”
Section: Discussionmentioning
confidence: 61%
“…National Center for Health Statistics (NCHS) reference children. On the other hand, some authors have found small urban-rural differences in growth, compared to differences among social strata (Martorell and Habicht, 1985;Mendez Castellano, 1985;Singh et al, 1987;Lopez Blanco et al, 1987;Landaeta-Jimenez et al, 1991).…”
mentioning
confidence: 98%